Effect of austenitic stainless steel weld clad layers on conduction heat transfer across the walls of pressure vessels. (June 2022) - Sowrirajan, M; Vijayan, S; Arulraj, M.; Babu, N Vinoth
Cladding austenitic stainless steels are popular nowadays in pressure vessels to enhance surface qualities. In this work, austenitic stainless-steel clad layers deposited by flux cored arc welding process on structural steel plates used in boiler construction are investigated in the direction of heat energy conservation. This study is vital, as the low thermal conductivity of austenitic stainless-steel clad layer is capable of reducing heat transfer across walls of pressure vessels. Heat transfer studies were performed using theoretical approach, computational simulations and experimental approach. Results of these studies exhibit a heat conservation of 10.6% owing to the stainless-steel clad layers with optimum clad thickness. The results of theoretical and computational method are having good agreement with the experimental results. These dual-benefit findings of the present work could be supportive to impart corrosion resistance and energy conservation, thereby, in energy efficient design of the thermal equipment.